2015
DOI: 10.1007/s00590-015-1607-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of compression in the management of soft tissue ankle injuries: a systematic review

Abstract: Compression may be an effective tool in the management of ankle injuries and has been shown to reduce swelling and improve quality of life in single studies. Definitive conclusions are hampered by the poor quality of evidence and the variety of treatments used. The most effective form of compression to treat ankle sprains or is yet to be determined. Adequately designed randomized control trials are clearly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…25 Compression therapy after ankle fracture has a beneficial effect on edema reduction and pain, but whether the effect on wound healing and length of time is similar remains inconclusive after multiple reviews. 1,26,27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Compression therapy after ankle fracture has a beneficial effect on edema reduction and pain, but whether the effect on wound healing and length of time is similar remains inconclusive after multiple reviews. 1,26,27…”
Section: Discussionmentioning
confidence: 99%
“…25 Compression therapy after ankle fracture has a beneficial effect on edema reduction and pain, but whether the effect on wound healing and length of time is similar remains inconclusive after multiple reviews. 1,26,27 For reduction of acute and chronic swelling after trauma and surgery of the foot and ankle, a pneumatic intermittent impulse compression device was demonstrated to be effective. 28,29 We demonstrated that swelling of the overall upper extremity was mostly reduced on day 3, with a reduction of 17.34%.…”
Section: Discussionmentioning
confidence: 99%
“…Compression is advocated for treating ACEJIs such as ankle sprains to limit swelling 7,37 and to improve quality of life. 37 In theory, compression, both circumferential and sequential, is applied to limit the amount of edema caused by the exudation of fluid from the damaged capillaries [38][39][40] and prevent possible hypoxic damage to surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, focal compression directed to the soft tissue around the fibular malleolus appears to reduce edema, assisting with increased function over time, which is why compression was used in conjunction with the MC technique [40]. However, compression has yet to be identified as making a substantial impact on acute ankle sprain recovery, in high-quality randomized control trials [41]. Compression is identified as Category C Evidence by the NATA, meaning the recommendation is based on limited evidence consisting of case series, opinions, and usual practice [25].…”
Section: Discussionmentioning
confidence: 99%